15-Deoxy-Isoxeniolide-A, New Diterpenoid from a Bornean Soft Coral, Xenia sp. - Chin-Soon Phan; Takashi Kamada; Kazushi Kobayashi; Toshiyuki Hamada; Charles Santhanaraju Vairappan (2018)
A new xenicane diterpenoid, 15-deoxy-isoxeniolide-A (1) along with four known compounds 9-deoxy-isoxeniolide-A (2), isoxeniolide-A (3), xeniolide-A (4) and coraxeniolide-B (5) were isolated from the Bornean soft coral Xenia sp. The structure of this metabolite was elucidated on the basis of spectral analysis NMR and HRESIMS. Compound 5 showed potent cytotoxic activity against ATL cell line, S1T.